Islamic Late Antiquity and Fatḥ: the Effect as Cause - Emilio González Ferrín (Araucaria. Revista Iberoamericana de Filosofía, Política y Humanidades, 2019)
The aim of this paper is to reconsider the very concept of Fatḥ -conquest- as means of early Islamic expansion as well as the way we tend to describe so many war actions in the Middle East and the Mediterranean region, the seventh and the eighth centuries, sometimes as Islamic, sometimes as Arab futūḥ -conquests-. It will also focus on the inappropriateness of considering those several war actions –those futūḥ, to literary effects in later Arabic chronicles- as a chain of subsequent events, interrelated, centralized and derived from a single cause, i.e. the matrix of Islam, as it is usually considered and taught.